Learning and adapting: the use of monitoring and evaluation in countering violent extremism: a handbook for practitioners - and Dawson, Laura; Edwards, Charlie; Jeffray, Calum (Royal United Services Institute for Defence and Security Studies, 2014)
IN 2013, the Royal United Services Institute for Defence and Security Studies (RUSI) was awarded a grant under the Kanishka Project to develop a handbook for monitoring and evaluating counter violent extremism (CVE) policies and programmes. The aim of this handbook is to support CVE policy-makers and practitioners (those who design, manage and evaluate CVE programmes), by providing them with key terms regarding violent extremism and radicalisation, describing the purpose of evaluation, and providing examples of key methodologies they can employ to conduct monitoring and evaluation (M&E) in this emerging policy field. The handbook will enable readers to understand why, when and how to conduct an evaluation of a CVE policy, programme or project. .